129. Antimicrobial Stewardship Intervention Bundle Decreases Fluoroquinolone Prescribing for Urinary Tract Infection in Urgent Care and Primary Care Clinics. (31st December 2020) - Cubillos, Ashley L; Caulder, Elisabeth; Patch, Megan; Saunders, Mary B; Lynch, Leah W; Gieselman, Morris R; Calkins, Karen
Abstract: Background: Fluoroquinolone antibiotics are associated with a number of serious adverse effects, and are not recommended for use in uncomplicated infections, including urinary tract infections (UTIs), where other reasonable antibiotic alternatives exist. This analysis describes the impact of a multi-interventional antimicrobial stewardship initiative on outpatient fluoroquinolone prescribing rates for UTI within a large community health system across a variety of practice settings. Methods: Interventions included prescriber education, standardized order sets, and monthly feedback on fluoroquinolone prescribing rates in UTI at the prescriber level (for urgent care clinics) or clinic level (for primary care/internal medicine/employee health clinics). To assess the impact of these interventions, total fluoroquinolone prescribing rate in UTI patients was compared for defined 6-month time periods pre- and post-intervention implementation. Results: Fluoroquinolone prescriptions from urgent care clinics within our health system (N=4) for patients with a primary diagnosis of UTI decreased significantly, from 660/3081 (17.6%) in the pre-intervention period to 111/3641 (3%) in the post intervention period (P< 0.0001). Prescribing in primary care, internal medicine, and employee health clinics (N=19) decreased from 492/2071 (23.8%) to 156/2287 (6.8%) (P< 0.0001). Conclusion: A multi-interventional initiative to reduce the utilization of fluoroquinolone antibiotics resulted in decreased prescribing rates of these agents for UTI across a variety of outpatient practice settings. Disclosures: All Authors : No reported disclosures